Hungarian Monitoring, 28 January 1990 . [Magyar rádiófigyelő], 1990. január 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - 150,000 people demonstrate in Bucharest - Polish United Workers' Party splits into a number of factions - Czechoslovak CP about to split - GDR wants a government of administration above parties - More demonstrations in Czechoslovakia against the presence of Soviet troops in the country Domestic Affairs: - Imre Pozsgay in Israel - Soviet troop withdrawals - Romanian-Hungarian relations: Károly Király, "Welcome Romania" gala program, Cluj summer university Economy: - Independent Smallholders', Agrarian Workers and Civic Party (FKGP) petition to suspend land sales Külpolitika: - Estére már 150,000-en tüntettek Bukarestben - Több részre szakadt a LEMP - Szakadás előtt áll a csehszlovák kommunisták pártja - Pártok feletti ügyvezető kormányt akarnak az NDK-ban - Újabb tüntetés a szovjet csapatok jelenléte ellen Csehszlovákiában Belpolitika: - Pozsgay Imre Izraelben - Szovjet csapatkivonás - Román - Magyar kapcsolatok: Király Károly, Üdvözlünk Románia - Gálaműsor, kolozsvári magyar egyetem Gazdaság: - FKGP aláírásgyűjtés a földeladás felfüggesztése érdekében